Safety, Tolerability, and Pharmacokinetics of Benralizumab: A Phase 1, Randomized, Single-Blind Study of Healthy Chinese Participants - Cheung TT; Mai TH; Chia YL; Yap DYH; Lee CH; Chen CC; Huang Y; Jin Y; Johnston J; Werkström V; Yao Y; Ge X; et al. (Drug Design, Development and Therapy, 2023)
Tommy Tsang Cheung,1,* Tu H Mai,2,* Yen Lin Chia,2 Desmond YH Yap,1 Chi-Ho Lee,1 Cecil Chi-Keung Chen,2 Ying Huang,3 Yuwen Jin,3 James Johnston,4 Viktoria Werkström,5 Yuhui Yao,6 Xiaoyun Ge,7 Wenying Zheng8 1Department of Medicine, Queen Mary Hospital, The University of Hong Kong, Hong Kong, People’s Republic of China; 2Clinical Pharmacology and Quantitative Pharmacology, Clinical Pharmacology & Safety Sciences, BioPharmaceuticals R&D, AstraZeneca, South San Francisco, CA, USA; 3Clinical Pharmacology, R&D China, AstraZeneca, Shanghai, People’s Republic of China; 4Late-stage Development, Respiratory & Immunology, BioPharmaceuticals R&D, AstraZeneca, Cambridge, UK; 5Late-Stage Development, Respiratory & Immunology, BioPharmaceuticals R&D, AstraZeneca, Gothenburg, Sweden; 6Respiratory & Immunology, R&D China, AstraZeneca, Shanghai, People’s Republic of China; 7Clinical Safety, R&D China, AstraZeneca, Shanghai, People’s Republic of China; 8Biometrics, R&D China, AstraZeneca, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yen Lin Chia, Clinical Pharmacology and Quantitative Pharmacology, Clinical Pharmacology & Safety Sciences, BioPharmaceuticals R&D, AstraZeneca, 701 Gateway Blvd, South San Francisco, CA, 9408, USA, Tel +1 425 5272574, Email yenlin@gmail.comPurpose: Biological therapies targeting eosinophils have been shown to be effective in treating patients with severe eosinophilic asthma. Benralizumab (Fasenra®, AstraZeneca) is a humanized monoclonal antibody binding to the alpha subunit of the interleukin-5 receptor, which rapidly depletes eosinophils via antibody-dependent cellular cytotoxicity. The aim of this Phase 1 study was to assess the safety, tolerability, and pharmacokinetics of benralizumab in healthy Chinese individuals.Materials and Methods: In this randomized, single-blind study (NCT03928262), healthy Chinese adult participants aged 18 to 45 years, weighing 50 to 100 kg, were randomized 1:1:1 to receive a single subcutaneous (SC) injection of benralizumab 10 mg, 30 mg, or 100 mg in the upper arms on Day 1. Safety was monitored throughout the study (up to Day 85), and blood samples were taken to determine serum benralizumab concentrations and for detection of anti-drug antibody. A non-compartmental analysis was conducted to estimate the pharmacokinetic parameters.Results: Thirty-six healthy participants were enrolled, 12 in each dose group (mean [SD] age 26 [6] years). Following a single SC injection of benralizumab, 13 adverse events were reported by 10 participants (28%), with one mild injection-site reaction assessed as related. The mean serum benralizumab concentrations increased in a dose proportional manner, followed by exponential decreases. The mean terminal half-lives were 15.1 days for the 10 mg dose, 14.4 days for the 30 mg dose, and 15.4 days for the 100 mg dose. All doses resulted in near-complete depletion of eosinophils on Day 2, which was maintained throughout the study to Day 85.Conclusion: A single SC injection of benralizumab was well tolerated by healthy Chinese participants, with no new or unexpected safety findings. The pharmacokinetics of benralizumab in Chinese participants was dose-proportional and consistent with those of non-Chinese participants observed in previous studies.Clinical Trial Registration: NCT03928262 (https://clinicaltrials.gov/ct2/show/NCT03928262)Keywords: benralizumab, pharmacokinetics, healthy Chinese